The Premillennial Menace - Case, Shirley Jackson (The biblical world, 1918)
To divide Christians by appeal to theological differences in these days savors of disloyalty. We need unity of religious spirit if our national morale is to be strong and hopeful. But the present crusade of premillenarians is not a matter of mere theology. It strikes at the heart of our religion if not of our patriotism. For this reason we discuss it. An assault upon our faith in a God who works through human ideals and national sacrifice for the sake of a better world is too dangerous to be permitted without protest and exposure. Professor Case writes with the facts before him, without bitterness but with warning. Since his paper has been put in type the newspapers report that several of the leaders of one of these movements have been found guilty of disloyal utterances and sentenced to imprisonment.